Maternal and child nutrition and development in Balaka and Ntcheu districts: Findings from MAZIKO inception studies - Save the Children (Save the Children, 2023)
MAZIKO is a five-year integrated Maternal and Child Grant pilot project targeting mothers and children under five years in eight Traditional Authorities in Balaka and Ntcheu districts. The aim of the project is to improve child growth and development by combining government recommended multi-sectoral social and behaviour change, and capacity strengthening interventions, with monthly cash transfers to improve maternal and child nutrition and development outcomes. In the first year of the programme, several qualitative and quantitative studies were conducted to inform the design of the project. These included a) a baseline quantitative survey targeting 2,686 households with a pregnant woman or child under 2 years in 262 villages; b) a qualitative study, using immersion research and people centered design approaches in 12 households with a pregnant woman or child under 2 years; c) a district capacity assessment to identify bottlenecks in service provision for nutrition and early child development; and d) a Cost of the Diet study to estimate the cost and affordability of a nutritious diet and the role that cash transfers can play to reduce the affordability gap. All studies were done in Ntcheu and Balaka, while the Cost of Diet study used national data. Key findings across the studies are summarised below, followed by more detailed findings for each study.